Modulatory effects of gut microbiome in cancer immunotherapy: A novel paradigm for blockade of immune checkpoint inhibitors. (25th December 2020) - Rezasoltani, Sama; Yadegar, Abbas; Asadzadeh Aghdaei, Hamid; Reza Zali, Mohammad
Abstract: The human gastrointestinal (GI) tract harbors gut microbiome, which plays a crucial role in preserving homeostasis at the intestinal host‐microbial interface. Conversely, specific gut microbiota may be altered during various pathological conditions and produce a number of toxic compounds and oncoproteins, in turn, to induce both inflammatory response and carcinogenesis. Recently, promising findings have been documented toward the implementation of certain intestinal microbiome in the next era of cancer biology and cancer immunotherapy. Notably, intestinal microbiota can cooperate with immune checkpoint inhibitors (ICIs) of its host, especially in enhancing the efficacy of programmed death 1 (PD‐1) protein and its ligand programmed death ligand 1 (PD‐L1) blockade therapy for cancer. Herein, we review the dual function of gut microbiota in triggering GI cancers, its association with host immunity and its beneficial functions in modulation of cancer immunotherapy responses. Furthermore, we consider the significance of gut microbiota as a potential biomarker for predicting the efficacy of cancer immunotherapy. Finally, we summarize the relevant limitations that affect the effectiveness and clinical applications of gut microbiome in response to immunotherapy. Abstract : In this review, we discuss the dual role of gut microbiome in triggering GI cancers, its association with host immunity and its beneficial functions in modulation of cancer immunotherapy responses. Furthermore, we consider the significance of gut microbiota as a potential biomarker for predicting the response to immunotherapy.